Identification of Weak Zones with Resistivity Values Using Electrical Resistivity Imaging (ERI) in Bentiring Subdistrict, Bengkulu - Adrian Daniel; Halauddin Halauddin; Suhendra Suhendra; Muhammad Taufik Apriadi; Agung Wijaya; Lulu Indah Setyawati; Hana Raihana (Jurnal Fisika Unand, 2026)
Bentiring Subdistrict is dominated by alluvial rock with a low water table depth, causing several roads and houses to experience subsidence and tilting, which may indicate the presence of a weak zone. The purpose of this study was to identify the presence of a weak zone based on resistivity values using the electrical resistivity imaging (ERI) method. This study utilised the ERI method with a Wenner Schlumberger configuration. The results showed that there was a weak zone on track 1 at a depth of 10.3-78.8 metres, with resistivity values of 12.3-28.2 Ωm. On track 2, subsidence was suspected at a depth of 3-39.6 metres, on track 3, the subsidence is located at a depth of 2.50-57.3 and 2.50-45.5 metres, on track 4, the subsidence is located at a depth of 10.8-67.3 meters, and on track 5, the subsidence is located at a depth of 10.3-57.3 metres. Weak zones are found on track 1 at a depth of 10.3-78.8 metres, where the constituent rock layer is sandy claystone. On tracks 2, 3, 4, and 5, there are subsidence areas with varying resistivity values ranging from 8.78 to 96 Ωm at depths ranging from 2.7 to 78.8 meters.